Cation exchange process on copper selenide for HER/OER catalyst - Li, Jiuwei (2019)
Although fossil fuels play a crucial role in modern society, the burning of fossil fuels will cause air pollution and emitter of carbon greenhouse gases such as carbon dioxide (CO2). Meanwhile, the increasing demand for energy in today’s society makes fossil energy insufficient. Therefore it’s necessary and urgent demand for sustainable and environmental friendly energy supply. Hydrogen has attracted people’s attention because of the outstanding conversion efficiency without generation of greenhouse gases. It can be produced by splitting of water with the help of electrocatalyst. Currently, high-efficiency catalysts are made of precious metals, for instance the platinum and iridium oxide for hydrogen evolution (HER) and oxygen evolution reaction (OER). However, the shortage and expensive prices prevent their widespread application in modern industry. Thus, developing a commercial catalyst with high efficiency to replace expensive precious metal-based catalysts and increase electrochemical reaction efficiency is an urgent thing.